Managing motivation in the Chinese family business - Wen, Boyun (2016)
Employees may have low motivation attitudes since management system is not perfect in most family business. Moreover, both family member and non-family member may have the conflicts to a great extent, because most non-family members may feel inequality in job position and their promotion opportunities could be affected (Jia 2013). In addition, most managers are charged by male employees, they may have more prejudice and stereotyping for female (Singh, Finn and Goulet 2004). Hence, female employees’ working motivation and performance may be impacted by gender discrimination. Additionally, employees’ motivation may be influenced based on their job natures, educational level and individual background (Geng 2004; Yang, Fang and Ling 2003; Jia 2013). Therefore, on the basis of this, managers may need to take into consideration applying various motivation methods so that employees’ different demands could be satisfied.